2021
DOI: 10.7717/peerj-cs.721
|View full text |Cite
|
Sign up to set email alerts
|

IoT-based intrusion detection system using convolution neural networks

Abstract: In the Information and Communication Technology age, connected objects generate massive amounts of data traffic, which enables data analysis to uncover previously hidden trends and detect unusual network-load. We identify five core design principles to consider when designing a deep learning-empowered intrusion detection system (IDS). We proposed the Temporal Convolution Neural Network (TCNN), an intelligent model for IoT-IDS that aggregates convolution neural network (CNN) and generic convolution, based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Data clustering The existing deep learning-based intrusion detection methods usually directly map the preprocessed one-dimensional numerical features into corresponding two-dimensional matrices and fill the redundant parts with zeros [33]. Although this method is simple and straightforward, it ignores a fundamental issue -the added relevance (Aljumah, A., 2021). The transformed two-dimensional matrix is similar to a grayscale image and inevitably imposes a correlation in the vicinity of the matrix elements.…”
Section: Fig2: Block Diagram Of the Proposed Idsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data clustering The existing deep learning-based intrusion detection methods usually directly map the preprocessed one-dimensional numerical features into corresponding two-dimensional matrices and fill the redundant parts with zeros [33]. Although this method is simple and straightforward, it ignores a fundamental issue -the added relevance (Aljumah, A., 2021). The transformed two-dimensional matrix is similar to a grayscale image and inevitably imposes a correlation in the vicinity of the matrix elements.…”
Section: Fig2: Block Diagram Of the Proposed Idsmentioning
confidence: 99%
“…However, there are still a large number of research gaps that still need to be identified from previous solutions. Some of these are (Aljumah, A., 2021):…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations